O FLORESCER DA CULTURALIDADE NA EDUCAÇÃO DO CAMPO: CONTRIBUIÇÕES DA PESQUISA BASEADA EM DESIGN - Vargas, Andressa Franco (2024)
This thesis aims to structure, apply and investigate what characteristics a training process should have, permeated by cultural and methodological issues of the rural context, that promote the professional development of teachers who work in Rural Education. The justification for this investigation emerges from research results on the topic that point to the need to look at the teacher and the challenges of teaching practice in rural schools. To achieve the proposed objective, we organized this research following the assumptions of Design-Based Research (PDB) in terms of methodological approach. PBD is an approach that is based on real contexts that can be investigated based on observed problems. Thus, we highlight the tripod proposed by McKenney and Reeves (2019) which highlights the path of research of this nature, proposing three phases: I) Analysis and exploration; II) Design and construction and III) Assessment and Reflection. For the Analysis and Exploration of the problems of this project, four actions were organized, they are: a) Application of a questionnaire with teachers who teach in the field; b) Application of a questionnaire with teachers who teach in the Degree in Rural Education; c) Analysis of research on the topic and d) Literature Review. When analyzing the results of the actions carried out, we highlight at least 17 partial results that portray the lack of continuing education courses that meet the specificities of the field context and the report of teachers who, at times, feel helpless and insecure when making adaptations to their practice because they do not have specific knowledge about their context of activity. Moving on to Design and Construction I, we explore solutions, define preliminary design principles and structure the prototype model for the first application of the training process with experts. In Assessment and Reflection I, we present the vision of these experts and refine the continuing education course model for a second cycle, returning to the second phase of PBD. Therefore, in what we call Design and Construction II, we present the prototype of the course in its version for application with a group of teachers who work in rural schools, expanding proposals from each moment and incorporating conceptual issues, narratives and the relationship of teacher’s belonging and their workspace. After these modifications, we proceed to Assessment and Reflection II, in which, through Discursive Textual Analysis, we analyze whether the course, when applied with a group of rural teachers, provided support for the learning and professional development of the participants. At this stage we present speeches, reflections and some notes on how the course can still be improved to achieve the objectives and characteristics of professional development considered necessary. And, after this cycle, we finish with another redesign of the prototype for a third cycle that can be applied at a later time and if the design principles have been confirmed. In our study, it was possible to confirm one of the principles, confirm two with changes and create one more, understanding the importance of making them more comprehensive and embracing the research needs. As final considerations of this thesis, we point out that it was possible to confirm the initial problem as a broad educational problem that gave us support for complex research, furthermore, that the objective was fulfilled, since it was possible to refine the structure of the process at least twice formative. Thus, we consider that the thesis presented here is about stating that a collaborative group can offer moments of reflection, construction of proposals, collaborative work and help rural school teachers to develop professionally, understanding their workspace and their specificities.